Charge transport in mixed semiconducting carbon nanotube networks with tailored mixing ratios - Brohmann, Maximilian; Berger, Felix J.; Matthiesen, Maik; Schießl, Stefan Patrick; Schneider, Severin; Zaumseil, Jana (ACS nano, 2019)
The ability to prepare uniform and dense networks of purely semiconducting single-walled carbon nanotubes (SWNTs) has enabled the design of various (opto-)electronic devices, especially field-effect transistors (FETs) with high carrier mobilities. Further optimization of these SWNT networks is desired to surpass established solution-processable semiconductors. The average diameter and diameter distribution of nanotubes in a dense network were found to influence the overall charge carrier mobility; e.g., networks with a broad range of SWNT diameters show inferior transport properties. Here, we investigate charge transport in FETs with nanotube networks comprising polymer-sorted small diameter (6,5) SWNTs (0.76 nm) and large diameter plasma torch SWNTs (1.17-1.55 nm) in defined mixing ratios. All transistors show balanced ambipolar transport with high on/off current ratios and negligible hysteresis. While the range of bandgaps in these networks creates a highly uneven energy landscape for charge carrier hopping, the extracted hole and electron mobilities vary nonlinearly with the network composition from the lowest mobility (15 cm2 V-1 s-1) for only (6,5) SWNT to the highest mobility (30 cm2 V-1 s-1) for only plasma torch SWNTs. A comparison to numerically simulated network mobilities shows that a superposition of thermally activated hopping across SWNT-SWNT junctions and diameter-dependent intratube transport is required to reproduce the experimental data. These results also emphasize the need for monochiral large diameter nanotubes for maximum carrier mobilities in random networks.
Gesehen am 11.09.2019